Comparative Drug Utilization of Antimicrobial Agents in Medical and Respiratory Intensive Care Units of a Tertiary Care Teaching Hospital in South India - Benjamin, Bincy; Kumar, B Sajeev; Udaykumar, Padmaja; Swamy, V.B. Narayana (Indian Journal of Pharmacy Practice)
Introduction : Drug Utilization Evaluation play a key role in managing healthcare system to understand, interpret, evaluate and improve the prescribing, administration and use of medications. Objective: To evaluate and compare the drug utilization of antimicrobials in Medical and Respiratory Intensive Care Units so as to include restriction policies. Methods: A prospective, observational study was performed on 209 prescriptions. The total number of drugs, dose, route, sensitivity pattern and cost were collected from in-patient records. The Defined Daily Dose/100 bed days of the most frequently prescribed antimicrobials was also calculated. Results: Out of the 1046 drugs prescribed in the Medical Intensive Care Unit, 167 antimicrobials were prescribed with an average of 2 drugs per prescription. The average length of stay was 4 (±1.4) days. Frequently prescribed antimicrobials were ceftriaxone, amikacin and clindamycin. The DDD/100 bed days for those drugs was 22.2, 6.9 and 5.9 respectively. The widely prescribed combinations were piperacillin+tazobactam and cefoperazone+tazobactam. In only 23% of the cases sensitivity test was performed. The most prevailing organisms were E.Coli (53%) and Acinetobacter sps (23%). Colistin and meropenam were the most sensitive antimicrobials for most microorganisms. In Respiratory Intensive Care Unit, out of 1024 drugs, 163 antimicrobials were prescribed with an average of 2 drugs per prescription. The average length of stay was 4 (±1.4) days. Ceftriaxone (40%) was found to be most commonly prescribed drug followed by clindamycin (17%), levofloxacin (12%) and meropenam (11%). The generally prescribed combination was piperacillin+tazobactam (30%). The DDD/100 bed days was found to be high. In only 20% of the cases sensitivity test was performed. Acinetobacter sps was the most frequently isolated pathogen and all microorganisms were sensitive to colistin. Conclusion: There is a need of anti-microbial agents usage guidelines and restriction policies for the rational prescribing of antimicrobials in critically ill patients.
Keywords: Drug Use Evaluation; Antimicrobial Agents; MICU; RICU; Sensitivity pattern; Defined Daily Dose